The Foot Fault Scoring System to Assess Skilled Walking in Rodents: A Reliability Study - Martins, Lucas Athaydes; Schiavo, Aniuska; Xavier, Léder Leal; Mestriner, Régis Gemerasca (Frontiers in Behavioral Neuroscience, 2022)
The foot fault scoring system of the ladder rung walking test (LRWT) is used to assess skilled waling in rodents. However, the reliability of the LRWT foot fault score has not been properly addressed. This study was designed to address this issue. Two independent and blinded raters analyzed 20 rat and 20 mice videos. Each video was analyzed twice by the same rater (80 analyses per rater). The intraclass correlation coefficient (ICC) and the Kappa coefficient were employed to check the accuracy of agreement and reliability in the intra- and inter-rater analyses of the LRWT outcomes. Excellent intra- and inter-rater agreement was found for the forelimb, hindlimb and both limbs combined in rats and mice. The agreement level was also excellent for total crossing time, total time stopped and number of stops during the walking path. Rating individual scores in the foot fault score system (0 to 6) ranged from satisfactory to excellent, in terms of the intraclass correlation indexes. Moreover, we showed experienced and inexperienced raters can obtain reliable results if supervised training is provided. We conclude the LRWT is a reliable and useful tool to study skilled walking in rodents and can help researchers address walking-related neurobiological questions.